Sinnena, kyrkorna och skogen. Sensorisk arkeologi i Örkelljunga och Perstorps kyrka - Danielsson,Fabian (2025)
Danielsson, F. 2025. The senses, the churches and the forest: Sensory archaeology in Örkelljunga and Perstorps church. Medieval churches have been a foundational area of inquiry for the field of historical archaeology since its conception at Lund university in the 1960’s. Since then, plenty of studies have been conducted that examines medieval churches from a top-down approach while other aspects have been seen as secondary. In the last 20 years however, the affective turn has introduced new ways to investigate and interpret the past. This study aims to investigate how medieval churches in northern Scania created and changed sensory experiences and in what ways these sensory experiences shaped/changed the parishioners and the surrounding landscape. By applying theory and methods from the field of sensory archaeology the study also aims to discuss if sensory archaeology can provide new ways to interpret the medieval church material in Scania. The study concludes that the churches in Örkelljunga parish and Perstorp parish fundamentally changed the sensory landscape in the areas in which they were built. The churches affected all aspects of the human senses including, sight, hearing, smell, touch and taste. Additionally, this resulted in the fact that these sensory experiences were tied to and crucial for creating a sense of Christian community within the parish. Furthermore, I argue for the fact that this sensory landscape was imported willingly by the farmers that colonised these areas during the medieval period to legitimize and activate their Christian world view. Finally, I argue for the fact that sensory archaeology provides new ways to interpret churches from a bottom-up perspective that also provides new ways for historical archaeologists to produce research that appeals to a wider public.
Keywords: Sensory archaeology; churches; Örkelljunga; Perstorp.